Green Innovation & Green Competitive Advantage in the impact of Green Marketing Orientation on Purchase Intention on the Use of Fabric Shopping Bags in UMS Management Students - Eka Vina Damayanti; Jati Waskito (UM Purwokerto Press, 2024)
This study investigates how Green Innovation and Green Competitive Advantage contribute to the impact of Green Marketing Orientation on Purchase Intention on the Use of Fabric Shopping Bags in UMS Management Students. With the phenomenon that we've raised is that it's all about shopping using a totebag. The methods used in this research are quantitative research methods as well as sample selection using purposive sampling approaches. The research was conducted at the 2020 Military Management Students of Muhammadiyah University of Surakarta. The study used a sample of 150 students who had been confirmed and eligible for testing because they had passed the data checking phase. Where data is measured numerically and uses Structural Equation Modeling with Partial Least Square. SmartPLS 3.0 was utilized in this program. The findings of this study indicate that Green Competitive Advantage significantly affects Purchase Intention, Green Innovation significantly does not affect Purchase Intention, Green Marketing Orientation significantly affects Green Competitive Advantage, Green Marketing Orientation significantly affects Green Innovation, Green Marketing Orientation does not affect Purchase Intention, Green Competitive Advantage significantly provides a mediating effect on Green Marketing Orientation and Purchase Intention, Green Innovation significantly does not provide a mediating effect on Green Marketing Orientation and Purchase Intention.